Polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization and its use

The polyoxymethylene-based all-solid polymer electrolyte, prepared by in-situ ring-opening polymerization, addresses safety and performance issues in lithium batteries by providing high ionic conductivity and electrochemical stability, enhancing safety and energy density.

JP7599809B2Active Publication Date: 2024-12-16QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022539305
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-25
Filing Date
2020-02-12
Publication Date
2024-12-16
Estimated Expiration
2040-02-12

AI Technical Summary

Technical Problem

Existing lithium batteries face safety hazards due to heat release and fire risks from liquid electrolytes, limited electrochemical windows, poor compatibility with high-voltage cathode materials, and low ionic conductivity, especially at room temperature, which restrict their application in electric vehicles and mobile devices.

Method used

A polyoxymethylene-based all-solid polymer electrolyte is prepared by in-situ ring-opening polymerization, using a trioxane-based monomer, lithium salt, and additive on a porous support material, achieving an ionic conductivity of 4×10⁻⁵ S/cm to 8×10⁻³ S/cm and an electrochemical window of 4.2 V or higher.

Benefits of technology

The electrolyte enhances safety by suppressing lithium dendrite growth, improves interfacial stability, and increases energy density, with excellent mechanical properties and long-cycle characteristics, suitable for high-voltage cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599809000003
    Figure 0007599809000003
  • Figure 0007599809000004
    Figure 0007599809000004
  • Figure 0007599809000005
    Figure 0007599809000005
Patent Text Reader

Abstract

The present invention relates to an all-solid-state polymer electrolyte, specifically to a polyoxymethylene-based all-solid-state polymer electrolyte prepared by in situ ring-opening polymerization and its use in the manufacture of all-solid-state lithium secondary batteries. The all-solid-state polymer electrolyte is prepared by in situ ring-opening polymerization of a trioxane-based monomer, an additive, and a lithium salt on a porous support material using a catalyst, and has a thickness of 10 μm-800 μm and an ionic conductivity of 4×10 at room temperature. -5 S / cm-8×10 -3 S / cm and an electrochemical window of 4.2 V or more. The all-solid-state polymer electrolyte of the present invention is easy to prepare, easy to mold, has excellent mechanical properties, and has high room-temperature ionic conductivity. In addition, this all-solid-state polymer electrolyte can effectively inhibit the growth of lithium dendrites, is compatible with positive electrode materials with relatively high voltages, and can effectively improve interface stability, long cycle characteristics, and energy density.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state polymer electrolyte, in particular to a polyoxymethylene-based all-solid-state polymer electrolyte prepared by in situ ring-opening polymerization and its use in producing an all-solid-state lithium secondary battery. [Background technology]

[0002] Lithium batteries used in application scenarios such as electric vehicles and mobile smart devices not only need to meet the requirements of long driving range, high-power charging and discharging, and long standby time, but also have very important safety performance. Currently, when liquid electrolyte-based lithium batteries are abused, short-circuited, or used under extreme working conditions, the contact between the positive and negative electrodes will cause a large amount of heat to be released inside the battery, resulting in fire and even the release of organic electrolyte, which will cause serious safety issues such as fire and explosion, greatly threatening the safety and experience of users. Therefore, although it is obvious that liquid electrolyte-based lithium batteries are difficult to realize, they need to be improved in terms of safety performance as soon as possible in order to realize more widespread applications. Even Tesla cars in the United States, which are currently considered the safest, have adopted complex battery management systems and safety measures, but in just a few years, there have been many accidents such as fires and explosions in electric vehicles. In addition, organic electrolytes also have the following problems: They have a limited electrochemical window and poor compatibility with metallic lithium anodes and newly developed high-voltage cathode materials. Lithium ions are not the only carriers, and when a large current flows, the internal resistance of the battery increases rapidly due to the ion concentration gradient (concentration polarization), causing the battery's performance to decline. There is a limit to the operating temperature (safe operating temperature is 0℃-40℃). As it reacts with the negative electrode material to produce a solid electrolyte interface (SEI) layer, active lithium and electrolyte are continuously consumed, and the battery capacity continues to decline. It is expected that the above problems can be fundamentally solved by using a solid electrolyte instead of an organic liquid electrolyte. A lithium battery formed in this way is called a solid-state lithium battery.

[0003] There are two types of solid-state lithium secondary batteries according to the solid electrolyte. One is a lithium battery made of a solid polymer electrolyte, also called a solid polymer lithium battery. The other is a lithium battery made of an inorganic solid electrolyte, also called an inorganic solid lithium battery. In the polymer electrolyte, the polymer base material mainly includes polyethylene oxide, polycarbonate, polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinylidene chloride, etc. Examples of disclosed polymer electrolytes are as follows: US4792504 discloses a polymer electrolyte containing polyethylene glycol dimethacrylate / polyethylene oxide, but its mechanical properties are not high; CN200710144760 discloses a polymer electrolyte in which ultrafine powder filler is added to polyethylene oxide, which has good mechanical properties but not high ionic conductivity; CN1428363A discloses a nanopore polymer electrolyte membrane, which has good charge / discharge and cycle properties. The polymer electrolyte membranes disclosed in the above two patents have good properties, but are gel polymer electrolytes.CN105826603A discloses a vinylene carbonate-based solid polymer electrolyte by in-situ polymerization and its use, which has good mechanical properties, but the solid polymer electrolyte has low ionic conductivity at room temperature and cannot operate at room temperature.

[0004] Polyethylene oxide (PEO) / lithium salt electrolytes have been used in solid polymer lithium batteries, but there are still many problems to be solved from a practical point of view. The mechanical properties of linear and grafted polymers are poor, and it is difficult to fabricate independent self-supporting polymer films. Because the ionic conductivity of the network polymer is too low, this type of polymer solid electrolyte is only suitable for operation under high temperature or low current conditions, and it is difficult to apply it in practice at room temperature. The electrochemical window is narrow, it is difficult to be compatible with high voltage positive electrode materials, and the energy density of solid lithium batteries is low. Summary of the Invention [Problem to be solved by the invention]

[0005] It is an object of the present invention to provide a polyoxymethylene-based all-solid-state polymer electrolyte prepared by in situ ring-opening polymerization and its use in the manufacture of all-solid-state lithium secondary batteries. [Means for solving the problem]

[0006] In order to achieve the above object, the present invention employs the following technical means. A polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization, the all-solid polymer electrolyte being prepared by in situ ring-opening polymerization of a trioxane-based monomer, an additive, and a lithium salt on a porous support material by a catalyst, the all-solid polymer electrolyte having a thickness of 10 μm-800 μm and an ionic conductivity of 4×10 at room temperature. -5 S / cm-8×10 -3 S / cm and an electrochemical window of 4.2 V or higher, prepared by in situ ring-opening polymerization, a polyoxymethylene-based all-solid-state polymer electrolyte.

[0007] The mass percentage of the polyoxymethylene-based polymer in the electrolyte is 20%-40%, the mass percentage of the lithium salt in the polymer electrolyte is 5%-20%, the mass percentage of the additive in the polymer electrolyte is 5-25%, and the mass percentage of the porous support material in the polymer electrolyte is 50%-60%.

[0008] The mass percentage of the catalyst in the polymer electrolyte is 0%-5%.

[0009] The trioxane monomer in the polyoxymethylene polymer has a structure represented by general formula 1, [ka] In the formula, R1, R2, and R3 may be the same or different, and each independently represents -H, -F, -Cl, -Br, -I, or -C. x H 2x+1where x ranges from 1 to 5; the lithium salt is one or more of lithium bis(oxalato)borate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium dioxodifluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium borate difluorooxalate; The general formula of the additive is NC-(CH2) y -CN, where y ranges from 1 to 16; the catalyst is one or more of lithium difluoroborate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium dioxodifluorophosphate, aluminum chloride, ferric chloride, boron trifluoride, boron trifluoride etherate, phosphorus pentafluoride, niobium pentachloride, titanium tetrachloride, zinc chloride, aluminum trifluoromethanesulfonate, bismuth chloride, perchloric acid, tyrosine, boric acid, and acetic acid; The porous support material is one or more of polyethylene separator, polypropylene separator, nylon nonwoven membrane, seaweed fiber nonwoven membrane, cellulose nonwoven membrane, bacterial cellulose, glass fiber, polyethylene terephthalate thin film, polyimide nonwoven membrane, polyamide membrane, spandex membrane, and aramid membrane.

[0010] When the lithium salt is one or more of lithium difluorooxalate, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium dioxodifluorophosphate, the amount of catalyst used is 0%. In this case, the lithium salt added can also act as a catalyst. When the lithium salt is one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalato)borate, the amount of catalyst used is 0.1%-5%.

[0011] A method for preparing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization, comprising the steps of: a) uniformly mixing the trioxane monomer and the additive in the ratio, and then adding the lithium salt and the catalyst and stirring the mixture uniformly; b) dropping the homogeneously mixed mixture onto a porous support material and allowing it to completely wet out; c) heating the porous support material infiltrated with the mixture at 40° C.-110° C. for 0.05 h-100 h to in-situ ring-opening polymerize the mixture to obtain a polyoxymethylene-based all-solid-state polymer electrolyte; A preparation method comprising:

[0012] In step a), the trioxane monomer and additives are stirred at 40-110°C for 0.1-10 hours to be uniformly mixed, and then the lithium salt and catalyst are added, and the mixture is stirred at 40-100°C for 0.01-10 hours to be uniformly mixed to obtain a mixture.

[0013] Use of polyoxymethylene-based all-solid-state polymer electrolytes prepared by in situ ring-opening polymerization in all-solid-state lithium secondary batteries (all-solid-state lithium-ion batteries, all-solid-state lithium metal batteries, all-solid-state lithium-sulfur batteries).

[0014] The all-solid-state lithium secondary battery includes a positive electrode and a negative electrode, and an all-solid-state polymer electrolyte is between the positive electrode and the negative electrode.

[0015] The porous support material infiltrated with the mixture is placed between the positive and negative electrodes, and heated at 40°C-110°C for 0.05h-100h to polymerize the mixture in situ through ring-opening polymerization to obtain a polyoxymethylene-based all-solid-state polymer electrolyte, which is prepared by homogeneously mixing trioxane-based monomers and additives, followed by adding lithium salt and catalyst and stirring to homogeneously mix. Effect of the Invention

[0016] The present invention has the following advantages: The solid polymer electrolyte of the present invention is prepared by forming a room temperature deep eutectic precursor from a trioxane-based monomer and a nitrile-based monomer through in-situ polymerization. This precursor has good solubility in lithium salt. When a certain type of lithium salt is adopted, the polytrioxane-based all-solid polymer electrolyte prepared by in-situ ring-opening polymerization does not require the addition of a catalyst, and the lithium salt can act as a catalyst to initiate polymerization. A catalyst may be further added to further polymerize. The present invention has a simple method, a short time, and excellent room temperature ionic conductivity and a high electrochemical window.

[0017] The solid polymer electrolyte of the present invention is easily prepared, easily molded, has a thickness of 10 μm-800 μm, and has an ionic conductivity of 4×10 at room temperature. -5 S / cm-8×10 -3 S / cm and an electrochemical window of 4.2V or more. In addition, this solid electrolyte effectively inhibits the growth of dendrites in the lithium negative electrode, improving the interface stability and long cycle characteristics. The all-solid polymer electrolyte of the present invention has good mechanical properties, high room temperature ionic conductivity, and is effectively improved in interface stability, long cycle characteristics, and energy density by being used in combination with a positive electrode material having a relatively high voltage. [Brief description of the drawings]

[0018] [Figure 1] 1 is a digital photograph of the polytrioxane-based all-solid-state polymer electrolyte prepared by in situ ring-opening polymerization provided in Example 1 of the present invention. [Diagram 2] 1 is a digital photograph of the polytrioxane-based all-solid-state polymer electrolyte prepared by in situ ring-opening polymerization provided in Example 2 of the present invention before and after polymerization. [Diagram 3] FIG. 2 is a long-term cycle curve of a lithium iron phosphate / lithium metal battery assembled with a polytrioxane-based all-solid-state polymer electrolyte provided in Example 2 of the present invention; [Figure 4]4 is a discharge curve of a ternary material / lithium metal battery assembled with a polytrioxane-based all-solid-state polymer electrolyte provided in Example 3 of the present invention; [Diagram 5] FIG. 10 is a long cycle curve of a lithium cobalt oxide / lithium metal battery assembled with a polytrioxane-based all-solid-state polymer electrolyte provided in Example 8 of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The following examples further illustrate the present invention. Note that the following specific examples are merely for the purpose of explaining and illustrating the present invention, and are not intended to limit the present invention.

[0020] In order to solve many safety hazards of conventional liquid lithium ion batteries, such as electrolyte leakage, volatilization, easy combustion, and explosion, and at the same time, to solve the problem of the complicated molding process of gel polymer electrolyte, the present invention provides a polyoxymethylene-based all-solid-state polymer electrolyte prepared by in-situ ring-opening polymerization, thereby improving the comprehensive properties of conventional all-solid-state polymer secondary lithium batteries.

[0021] Example 1 In a glove box filled with argon gas, 4 g of paraldehyde and 1.5 g of succinonitrile were mixed uniformly on a hot plate at 60°C for 5 minutes, and then 0.375 g of lithium borate difluorooxalate was added and stirred for 10 minutes to mix uniformly (here, lithium borate difluorooxalate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst). 0.15 mL of the mixture was taken and dropped onto the cellulose support material. Then, LiCoO2 was used as the positive electrode and lithium as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive and negative electrodes. The assembled battery was heated at 60°C for 2 hours, and the mixture was polymerized in situ on the porous support material inside the battery to obtain an all-solid-state polymer electrolyte (Figure 1), and further an all-solid-state polymer lithium battery was obtained.

[0022] As can be seen from FIG. 1, the formed all-solid-state electrolyte was uniformly deposited on the cellulose nonwoven fabric separator.

[0023] Example 2 In a glove box filled with argon gas, 2.5 g of 1,3,5-trioxane (TXE) and 1.5 g of succinonitrile were stirred for 5 minutes on a hot plate at 80°C to mix uniformly, then 0.375 g of lithium borate difluorooxalate was added and stirred for another 5 minutes to mix uniformly (here, lithium borate difluorooxalate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst), 0.15 mL of the mixture was taken and dropped onto the cellulose support material, and then LiFePO4 was used as the positive electrode and lithium as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 80°C for 2 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid-state polymer electrolyte. A battery cycle test was performed using the all-solid-state polymer lithium battery. The battery charge / discharge range was 2.75 V to 4 V, the charge / discharge rate was 0.3 C, and the test temperature was room temperature (Figure 3).

[0024] As can be seen from FIG. 3, the all-solid-state electrolyte exhibited excellent cycle stability when lithium iron phosphate was used as the positive electrode and lithium was used as the negative electrode, with a capacity retention rate of 97% even after 100 cycles.

[0025] Example 3 In a glove box filled with argon gas, 2.5 g of 1,3,5-trioxane (TXE) and 2.5 g of succinonitrile were stirred for 10 minutes on a hot plate at 80°C to mix uniformly, then 0.375 g of lithium borate difluorooxalate was added and stirred for 5 minutes to mix uniformly (here, lithium borate difluorooxalate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst), 0.15 mL of the mixture was taken and dropped onto the cellulose support material, and then the ternary material was used as the positive electrode and lithium as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 80°C for 2 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid-state polymer electrolyte.

[0026] A battery cycle test was performed using the solid-state polymer lithium battery. The battery charge / discharge range was 2.75 V to 4.3 V, the charge / discharge rate was 0.2 C, and the test temperature was room temperature (Figure 4).

[0027] As can be seen from FIG. 4, when the ternary material (NCM22) is used as the positive electrode and lithium is used as the negative electrode, the discharge specific capacity of the all-solid-state electrolyte is 162 mAh / g under room temperature conditions, proving that the all-solid-state electrolyte has good interface compatibility with the ternary material and lithium and relatively high room temperature ionic conductivity.

[0028] Example 4 In a glove box filled with argon gas, 4 g of 1,3,5-trioxane (TXE) and 1.5 g of malonitrile were stirred for 20 minutes on a hot plate at 40°C to mix uniformly, then 0.4 g of lithium hexafluorophosphate was added and stirred for 2 minutes to mix uniformly (here, lithium hexafluorophosphate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst), 0.15 mL of the mixture was taken and dropped onto the cellulose support material, and then LiFePO4 was used as the positive electrode and graphite as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 40°C for 24 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid polymer electrolyte, and further obtaining a solid polymer lithium battery.

[0029] Example 5 In a glove box filled with argon gas, 2.5 g of 1,3,5-trioxane (TXE) and 2.4 g of succinonitrile were stirred for 40 minutes on a hot plate at 50°C to mix uniformly, then 0.375 g of lithium borate difluorooxalate was added and stirred for 5 minutes to mix uniformly (here, lithium borate difluorooxalate acts as both a lithium salt and a catalyst, so there is no need to add a catalyst separately), 0.4 mL of the mixture was taken and dropped onto the glass fiber support material, and then the ternary positive electrode material was used as the positive electrode and graphite as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 50°C for 10 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid-state polymer electrolyte, and further obtaining an all-solid-state polymer lithium battery.

[0030] Example 6 In a glove box filled with argon gas, 4 g of 1,3,5-trioxane (TXE) and 1.5 g of succinonitrile were stirred for 15 minutes on a hot plate at 60°C to mix uniformly, then 0.7 g of lithium tetrafluoroborate was added and stirred for 6 minutes to mix uniformly (here, lithium tetrafluoroborate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst), 0.4 mL of the mixture was taken and dropped onto a polyethylene terephthalate thin film, which is a support material, and then LiFePO4 was used as the positive electrode and lithium as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 60°C for 0.5 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid-state polymer electrolyte, and further obtaining an all-solid-state polymer lithium battery.

[0031] Example 7 In a glove box filled with argon gas, 4 g of 1,3,5-trioxane (TXE) and 1.5 g of glutaronitrile were stirred for 25 minutes on a hot plate at 40°C to mix uniformly, then 0.375 g of lithium borate difluorooxalate was added and stirred for 10 minutes to mix uniformly (here, lithium borate difluorooxalate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst), 0.2 mL of the mixture was taken and dropped onto the cellulose support material, and then sulfur was used as the positive electrode and lithium as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 40°C for 1 hour, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid-state polymer electrolyte, and further obtaining an all-solid-state polymer lithium battery.

[0032] Example 8 In a glove box filled with argon gas, 2.5 g of 1,3,5-trioxane (TXE) and 2.5 g of succinonitrile were stirred for 5 minutes on a hot plate at 80°C to mix uniformly, then 0.735 g of lithium borate difluorooxalate was added and stirred for 10 minutes to mix uniformly (here, lithium borate difluorooxalate acts as both a lithium salt and a catalyst, so there is no need to add a separate catalyst), 0.10 mL of the mixture was taken and dropped onto the cellulose support material, and then LiCoO2 was used as the positive electrode and lithium as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 80°C for 2 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery, thereby obtaining an all-solid-state polymer electrolyte, and further obtaining an all-solid-state polymer lithium battery.

[0033] A battery cycle test was performed using the solid-state polymer lithium battery. The battery charge / discharge range was 3V-4.3V, the charge / discharge rate was 0.3C, and the test temperature was room temperature (Figure 5).

[0034] As can be seen from FIG. 5, when 4.3 V lithium cobalt oxide was used as the positive electrode and lithium was used as the negative electrode, the all-solid-state electrolyte exhibited good cycle stability and high voltage resistance characteristics, with a capacity retention rate of 93% even after 100 cycles.

[0035] Example 9 In a glove box filled with argon gas, 1g of 1,3,5-trioxane (TXE) and 2g of succinonitrile were stirred for 15 minutes on a hot plate at 40°C to mix uniformly, then 1.5g of succinonitrile, 0.1g of LiPF6 (as a catalyst), and 0.4g of lithium bis(oxalato)borate were added and stirred for 10 minutes to mix uniformly, 0.15mL of the mixture was taken and dropped onto the cellulose support material, and then LiCoO2 was used as the positive electrode and graphite as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode, and the assembled battery was heated at 80°C for 1 hour, whereby the mixture was polymerized in situ on the porous support material inside the battery to obtain an all-solid-state polymer electrolyte, and further, an all-solid-state polymer lithium battery was obtained.

[0036] Example 10 In a glove box filled with argon gas, 2.5 g of 1,3,5-trioxane (TXE) and 1.5 g of succinonitrile were stirred for 5 minutes on a hot plate at 110°C to mix uniformly, then 0.1 g of lithium hexafluorophosphate (as a catalyst) and 0.4 g of lithium bis(oxalato)borate were added, and further stirred for 10 minutes to mix uniformly. 0.15 mL of the mixture was taken and dropped onto the cellulose support material. Then, LiCoO2 was used as the positive electrode and graphite as the negative electrode, and the porous support material infiltrated with the mixture was placed between the positive electrode and the negative electrode. The assembled battery was heated at 100°C for 0.5 hours, whereby the mixture was polymerized in situ on the porous support material inside the battery to obtain an all-solid-state polymer electrolyte, and further, an all-solid-state polymer lithium battery was obtained.

Claims

1. A method for producing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization, comprising: The all-solid-state polymer electrolyte is prepared by in situ ring-opening polymerization of a trioxane-based monomer, an additive, and a lithium salt on a porous support material under the influence of a catalyst, has a thickness of 10 μm-800 μm, and has an ionic conductivity of 4×10 at room temperature. -5 S / cm-8×10 -3 A method for producing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization, characterized in that the electrochemical window is 4.2 V or more and the electrochemical window is 4.2 S / cm.

2. The mass percentage of the polyoxymethylene-based polymer in the electrolyte is 20% to 40%; The mass percentage of the lithium salt in the polymer electrolyte is 5% to 20%; The mass percentage of the additive in the polymer electrolyte is 5-25%; The method for producing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization according to claim 1, characterized in that the mass percentage of the porous support material in the polymer electrolyte is 50%-60%.

3. The method for producing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization according to claim 1, characterized in that the mass percentage of the catalyst in the polymer electrolyte is 0%-5%.

4. The trioxane monomer in the polyoxymethylene polymer has a structure represented by general formula 1, 【Chemistry 1】 In the formula, R 1 , R 2 , R 3 may be the same or different, and each independently represents -H, -F, -Cl, -Br, -I, or C x H 2x+1 where x ranges from 1 to 5; the lithium salt is one or more of lithium bis(oxalato)borate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium dioxodifluorophosphate, lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium borate difluorooxalate; The general formula of the additive is NC-(CH 2 ) y -CN, where y ranges from 1 to 16; the catalyst is one or more of lithium difluoroborate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium dioxodifluorophosphate, aluminum chloride, ferric chloride, boron trifluoride, boron trifluoride etherate, phosphorus pentafluoride, niobium pentachloride, titanium tetrachloride, zinc chloride, aluminum trifluoromethanesulfonate, bismuth chloride, perchloric acid, tyrosine, boric acid, and acetic acid; The method for preparing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization according to any one of claims 1 to 3, characterized in that the porous support material is one or more of the following: polyethylene separator, polypropylene separator, nylon nonwoven membrane, seaweed fiber nonwoven membrane, cellulose nonwoven membrane, bacterial cellulose, glass fiber, polyethylene terephthalate thin film, polyimide nonwoven membrane, polyamide membrane, spandex membrane, and aramid membrane.

5. When the lithium salt is one or more of lithium difluorooxalate, lithium tetrafluoroborate, lithium hexafluorophosphate, and lithium dioxodifluorophosphate, the amount of catalyst used is 0%; The method for preparing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization according to claim 4, characterized in that when the lithium salt is one or more of lithium perchlorate, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium bis(oxalato)borate, the amount of catalyst used is 0.1%-5%.

6. A method for producing a polyoxymethylene-based all-solid polymer electrolyte prepared by the in situ ring-opening polymerization according to claim 1, comprising the steps of: a) uniformly mixing the trioxane-based monomer and the additive, and then adding a lithium salt and a catalyst thereto, and stirring the mixture uniformly; b) dropping the homogeneously mixed mixture onto a porous support material and allowing it to completely wet out; c) heating the porous support material infiltrated with the mixture at 40° C.-110° C. for 0.05 h-100 h to in-situ ring-opening polymerize the mixture to obtain a polyoxymethylene-based all-solid-state polymer electrolyte; A method for producing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization, comprising:

7. The method for preparing a polyoxymethylene-based all-solid polymer electrolyte prepared by in situ ring-opening polymerization according to claim 6, characterized in that in step a), the trioxane-based monomer and the additive are stirred and mixed uniformly under conditions of 40-110°C for 0.1h-10h, and then the lithium salt and the catalyst are added, and the mixture is stirred and mixed uniformly under conditions of 40-100°C for 0.01h-10h to obtain a mixture.

8. Use of the polyoxymethylene-based all-solid polymer electrolyte prepared by the in situ ring-opening polymerization according to claim 1 in all-solid lithium secondary batteries (all-solid lithium ion batteries, all-solid lithium metal batteries, all-solid lithium sulfur batteries).

Citation Information

Patent Citations

  • ion conductive polymer gel

    JP1994511595A

  • Polymer solid electrolyte precursor

    JP1999144760A

  • Electrolyte for electrochemical elements, method for manufacturing the same, and electrochemical elements equipped therewith

    JP2014504788A

  • Solid electrolyte, its preparation method and application

    JP2021514108A